Pendampingan Bimbingan Belajar Shalat Untuk Anak-Anak Di Dusun Jati Desa Krenceng Kecamatan Kepung - Hanik Nurfadhilah; Asyhari (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The obedience of one's worship is measured through the obligation to carry out religious orders such as the obligation to perform prayers. Prayer is a pillar of religion and it is the duty of Allah to be performed for a Muslim. If prayer is not established, the whole religion is lost. Educating or guiding children to learn to pray early on is an obligation because teaching children to pray from an early age makes it easier for children to understand and know about religion and religious values will begin to be nurtured and embedded in them. Prayer tutoring assistance programs for children have the hope that children can understand, learn and apply prayer correctly in everyday life.